Drivers of European Transition Countries' External Current Accounts: An LSDVC Approach - Stojkov, Aleksandar; Warin, Thierry (Eastern European economics, 2016)
The sizable and persistent external imbalances of European transition countries have attracted surprisingly little empirical attention. Although increasing external account deficits may be accompanied by accelerated growth rates, they also come with substantial risks. This article identifies and compares the main determinants of the widening and persistent external current account deficits of fifteen European transition countries vis-à-vis the EU-15 countries. It assesses the validity of the intertemporal approach of current account determination through bias-corrected least-squares dummy variable models (using three dynamic panel techniques) and data for thirty European countries during the 1994-2013 period. It concludes that the external accounts of European transition countries have been counter-cyclical and largely driven by faster growth of government consumption and investment as compared to their trading partners. After the outbreak of the global economic crisis, their external accounts improved due to lower private consumption and a significant rise in precautionary savings.